Understanding of temperature and cooling effectiveness sensitivity of a film-cooled vane under coolant inlet temperature effect: A case study - Prapamonthon, Prasert; Yin, Bo; Yang, Guowei; Zhang, Mohan (My University, 2019)
This work presents a case study of the relationship between temperature and cooling effectiveness of a film-cooled vane under effect of coolant inlet temperature in two aspects based on the actual and base coolant inlet temperatures. Results are conducted in terms of temperature, cooling effectiveness, and heat transfer coefficient based on surface and volume analyses using CFD/CHT approach. Sensitivity of the vane temperature and cooling effectiveness under this effect is discussed also. The results show that for the surface basis, although the cooling effectiveness obtained from the actual coolant inlet temperature is quite straightforward and follows the definition of the cooling effectiveness directly, the cooling effectiveness obtained from the base coolant inlet temperature is more understandable because it corresponds to the variation of the surface temperature. Based on the volume basis and the base coolant inlet temperature, the 8% increase in the coolant inlet temperature causes the reduction of the average and maximum cooling effectiveness, which corresponds to 18 K and 25 K increments in the average and minimum temperatures, respectively. However, when the actual coolant inlet temperature is used, the variation of the cooling effectiveness is rather insensitive due to the reduction of heat flux on the hot-side wall.
Keywords: Coolant inlet temperature; Cooling performance; Film cooling; Surface temperature